Songbooks : The Literature of American Popular Music - Weisbard, Eric (Book collections on Project MUSE., 2021)
"Songbooks, a critical guide to American popular music writing, unfolds chronologically, with entries on authors, artists, and topics beginning with William Billings's 1770 New-England Psalm-Singer. Outsiders proliferate in these pages: women and/or writers of color, authors displaced by sexuality, self-educated scholars, elites deviating from norms. Their work routinely took non-academic shapes: compilations of songs, memoirs and biographies, fiction and magazine essays. Others fought within the academy to establish fields like ethnomusicology and jazz studies. Drawing on his background as a Village Voice music critic and as the longtime organizer of the Pop Conference, Eric Weisbard offers an important corrective to a fragmented field"--